Faktor-Faktor Yang Berhubungan Dengan Tindakan Personal Hygiene Saat Mentruasi Pada Remaja Putri - Yulia Arifin; Ety Aprianty; Widya Wiguna (STIKes MERCUBAKTIJAYA, 2023)
Knowledge about personal hygiene during menstruation is closely related to reproductive health. Data from the 2017 Indonesian Health Demographic Survey (IDHS) showed that the practice of personal hygiene of adolescent girls during menstruation is still poor, namely 63.9% of Indonesian adolescent girls have improper personal hygiene during menstruation. The results of an initial survey at Darul Ulum Islamic Boarding School for 10 adolescent girls, there were 4 people who knew about personal hygiene actions during menstruation and of the 6 adolescent girls, the average changed pads only 2 times a day during menstruation This study aims to determine the relationship between knowledge and attitudes with personal hygiene actions during menstruation in adolescent girls at Pesantren Darul Ulum Padang. This study is an analytical descriptive study with a cross-sectional approach, and a sample of 49 adolescent girls at Pesantren Darul Ulum taken with systematic random sampling technique. The instrument used was a questionnaire with data analysis using univariate and bivariate tests with the Chi-Square test. The results showed that 57.1% had high knowledge, 53.1% had a positive attitude, 53.1% got information about personal hygiene and 65.3% had good personal hygiene. There is a relationship between knowledge (p=0.024), attitude (p=0.016) and getting information (p=0.003) with personal hygiene actions duringmenstruation. It is recommended for health workers to hold information and education counselling activities on personal hygiene actions during menstruation so that adolescent girls avoid the risk of ISR disease.